FAKTOR-FAKTOR PENYEBAB PERSELINGKUHAN SERTA TINDAK LANJUT MENGATASINYA - Suciptawati, Ni Luh Putu; Susilawati, Made (Jurnal Studi Jender SRIKANDI; Vol. 5, No. 2 Juli 2005, 2012)
A sample of 50 famele respondents in the age group 18-50 years in the city of Denpasar, shows that dominant factors considered as causes for extra-marital affairs are disharmony between the spouses, as well as economic, social and psychological factors. More than 50% of the respondents condemn their spouse for having an affair, but they prefer to forgive their patner instead of seeking a divorce.
Keywords: SELINGKUH